ADDRESSING GENDER INEQUALITY TO IMPROVE MATERNAL HEALTH IN INDONESIA: A NARRATIVE LITERATURE REVIEW - Putra, I Gusti Ngurah Edi (Proceedings of the International Conference on Applied Science and Health, 2019)
Introduction: High maternal mortality ratio (MMR) remains a pressing public health issue in Indonesia. Despite many studies have been conducted to identify the associated factors from medical and socio-cultural perspectives, fewer studies and discussion appeared to focus on another social dimension such as gender norms, which is not explored deeply in the context of Indonesia. Aims: This paper aimed to discuss how gender inequality affects maternal health in Indonesia and practical strategies needed to address gender inequality in improving maternal health outcomes in Indonesia.  Methods: This was a narrative literature review, based on several types of documents: research article, literature review, systematic review, books, and reports from institutions. Those would be reviewed and adjusted with the context of Indonesia in terms of how gender inequality affects maternal health, followed by the synthesis of argumentative ideas related to the practical strategies needed to address this issue.Results: The well-maintained patriarchal system and gender norms in Indonesia leads to gender inequality as one of the social factors contributing to maternal health outcomes. Gender inequality works to influence maternal health outcomes through structural and individual level factors, in which, influence women?s power and ability in the decision-making process and impact on women?s demand for maternal health service utilization. In addition, implemented maternal health programmes have not fully addressed gender inequality in Indonesia so far.Conclusion: To address gender inequality in order to improve maternal health, some strategies are suggested, such as women empowerment, men engagement to be supportive, and strengthening the protection of women?s reproductive rights.